The Dilemma of Pharmaceutical Companies in Pakistan: Navigating Price Regulations During a Time of High Inflation - Mansoor, Noman; Warsi, Aimen (Journal of the Pakistan Medical Association, 2023)
Dear Madam, An ever-worsening economic crisis, has hit Pakistan, and the political crisis and recent floods have added to the worsening situation [1]. The inflation rate in Pakistan has hit a record high of 35.4%, leading to the manufacturers’ increase in the cost of essentials and amenities [2]. However, pharmaceuticals have still not been allowed to increase their products’ prices, making it difficult for them to thrive, which has led to their decrease in number over the last few years [3]. Since 2018, the number of foreign pharmaceutical companies in Pakistan has been reduced from 48 to 22. [4]. The local sector is in no better position. Pakistan's pharmaceutical industry has warned that local businesses will have to cease due to extortionate production costs and the devaluation of the rupee, difficulties with imports, and rising inflation [5]. As many as 770 drug manufacturers in Pakistan have been impacted by the medicine shortage crisis consequent to a lack of essential raw products and materials imports [6]. More companies are expected to stop producing medicines owing to high costs in the upcoming days, which may lead to the number of scarce drugs in the country increasing from 500 to 2,500 [7]. Pakistan is the only country with a regulatory authority that controls the prices of all medicines. [8]. This entire situation has created an immense burden for consumers, who are compelled to face the consequence of medicine shortage, forcing them to buy medicines at a much higher cost. The deficit has also led to the production of counterfeit drugs, hurting not only the existing industries but also putting patients’ lives at very high risk. The industry's greatest worry is the complete freezing of pharmaceutical product prices. The government-set pricing structure prevents the pharmaceutical industry from raising the price of any drugs, even those whose costs have increased by more than 100%. With significantly increasing input, associated costs like fuel, electricity, labour, and raw materials have made it difficult for the industry to survive [8]. The government should pay immediate attention to this problem. The Drug Regulatory Authority of Pakistan (DRAP) needs to implement new policies allowing pharmaceutical to increase their products’ prices, ensuring not to overburden consumers with it. DRAP should be strengthened by upgrading to maintain global standards. ---Continue